Use of Some Biological Methods in the Integrated Pest Management Program (IPM) for Sesamia cretica - عفيف, علي; موسى السمارة,; نادين أسعد , (Latakia University Journal -Biological Sciences Series, 2024)
A semi-field experiment was conducted under greenhouse conditions in the village of Al-Sharashir - Jableh during the 2022-2023 season This is to test the effectiveness of the chemical pesticide Chromafenozide, the fungal isolate Beauveria bassiana b (8), and the aqueous extract of the Nerium Oleander plant This was done on two genetically different varieties of corn kernels: the Roy Soleil F1 variety and the Fayhaa variety, to combat the larvae of the large corn stalk borer, Sesamia cretica, under artificial infection conditions.The results of the statistical analysis showed that there were significant differences between the different treatments, as the infection rate of plants treated with the pesticide chromafenozide, the biocide B. bassiana b (8), and the aqueous extract of the Nerium Oleander plant reached 22.45%, 29.0%, and 37.6%, respectively, compared to the control 93.4%. The Roy Soleil variety also significantly outperformed the Fayhaa variety, as the infection rate of the Roye variety reached 39.9%, while the infection rate of the Fayhaa variety reached 51.3%. During the first week of pesticide spraying, the chemical pesticide chromafenozide excelled in reducing the infection rate of the stem borer S. cretica by 58.3%, while the biocide B. bassiana b (8) and the aqueous extract of oleander were able to reduce the infection rate of the borer by approximately 33.2% and 31.3%. Straight. During six weeks of spraying follow-up, it was found that there were significant differences between the pesticides, as the effectiveness of the chemical pesticide chromafenozide reached 83.5%, followed by the biopesticide Beauveria bassiana b (8) with an effectiveness of 74.7%, then the aqueous extract of the oleander plant with an effectiveness of 62.2% compared with the control.